2012
DOI: 10.1074/jbc.m111.295113
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of ADP-ribosylation Factor 6 in Toll-like Receptor 9-mediated Immune Signaling

Abstract: Background: ADP-ribosylation factor 6 is critical to a wide variety of cellular events, including vesicular trafficking and endocytosis. Results: Inhibition of ARF6 by dominant mutants and siRNA impaired CpG ODN/TLR9-mediated response. Conclusion: A novel class III PI3K-ARF6 axis pathway mediates TLR9 signaling by regulating the cellular uptake of CpG ODN. Significance: Determining the physiological roles of ARF6 in CpG ODN/TLR9-mediated responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…We find that TLR2-dependent NF-B activation is also independent of Arf6. In contrast, TLR9-dependent NF-B activation is strongly dependent on Arf6, as Arf6 regulates the internalization of CpG DNA (25,27). In this study, we show a similar effect of Arf6 on internalization of LPS, showed that Rab11a is required for transport of TLR4, Trif, Tram, and IRF3 to E. coli phagosomes (47).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…We find that TLR2-dependent NF-B activation is also independent of Arf6. In contrast, TLR9-dependent NF-B activation is strongly dependent on Arf6, as Arf6 regulates the internalization of CpG DNA (25,27). In this study, we show a similar effect of Arf6 on internalization of LPS, showed that Rab11a is required for transport of TLR4, Trif, Tram, and IRF3 to E. coli phagosomes (47).…”
Section: Discussionmentioning
confidence: 52%
“…In a similar way, TLR9 requires internalization of its ligand CpG DNA. Arf6 regulates this internalization of CpG DNA and is essential for TLR9 MyD88-dependent signal transduction (25). We therefore tested whether Arf6 modulation also affects the internalization of LPS.…”
Section: Blocking Arf6 Strongly Inhibits Lps-induced Irf3 Phosphorylamentioning
confidence: 99%
See 2 more Smart Citations
“…The assay was developed according to a method previously described (39). The detailed procedure is provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%